Fabrication of a hole transporting Cu2AgIn(S0.5Se0.5)4 nanoparticles deposited carbon counter electrode for perovskite solar cell. (15th August 2022) - Panneerselvam, Pratheep; Guo, JohnZhanhu; Angaiah, Subramania
Abstract: In the present study, a quaternary Cu-based chalcopyrite semiconductor, Cu2 AgIn(S0.5 Se0.5 )4 (CAISSe) nanoparticles (NPs) was synthesized by a hot injection method. X-ray diffraction (XRD) and Raman spectroscopy studies were carried out to finding the formation of tetragonal crystal structure of synthesized CAISSe NPs. HR-TEM analysis revealed the spherical morphology of the synthesized CAISSe NPs. The charge separation and carrier dynamics of the perovskite with CAISSe NPs deposited on pearl carbon were analyzed by photoluminescence (PL) studies. The intensity of PL spectrum was reduced for CAISSe NPs deposited on pearl carbon than the pristine pearl carbon. By adding sulfur with selenium influences, the device performance was further discussed. A comprehensive analysis of impedance spectroscopy was subsequently carried out to understand the charge transferring nature of perovskite/CAISSe@C CE interface. The higher PCE (η = 4.64%) is obtained for CAISSe NPs deposited pearl carbon CE based PSC than that of pristine pearl carbon CE based PSC (η = 2.69%). Graphical abstract: Image 1 Highlights: Cu2 AgIn(S0.5 Se0.5 )4 (CAISSe) nanoparticles (NPs) synthesized by a simple hot injection method. Structural and morphological properties of CAISSe NPs are studied. CAISSe NPs coated onto the pearl carbon CE and its influence is studied in detail. The highest PCE of 4.64% is obtained for CAISSe NPs deposited pearl carbon CE- than the pearl carbon CE- (η = 2.69%).